Arithmetic Aptitude :: Square Root and Cube Root

1 / 72

 In the polynomial f(x) =2*x^4 - 49*x^2 +54, what is the product of the roots, and what is the sum of the roots (Note that x^n denotes the x raised to the power n, or x multiplied by itself n times)?

Answer: Option A

Explanation:

The given equation is of type ax^4+bx^3+cx^2+dx+e.





Product of roots=(-1)^n*(coeff of constant term/coeff of x^4)= e/a = 54/2 =27



Sum of roots= -(coeff of x^3/coeff of x^4)= -b/a = -0/2=0

Workspace


Tags:  TCS

2 / 72

 If \(3\sqrt{5} + \sqrt{125}\) = 17.88, then what will be the value of \(\sqrt{80} + 6\sqrt{5}\) ?

Answer: Option D

Explanation:

\(3\sqrt{5} + \sqrt{125} = 17.88\)

\(\Rightarrow 3\sqrt{5} + \sqrt{25 \times 5} = 17.88\)

\(\Rightarrow 3\sqrt{5} + 5\sqrt{5} = 17.88\)

\(\Rightarrow 8\sqrt{5} = 17.88\)

\(\Rightarrow \sqrt{5} = 2.235\)

\(\sqrt{80} + 6\sqrt{5} = \sqrt{16 \times 5} + 6\sqrt5\)

= \(4\sqrt5 + 6\sqrt5\)

= \(10\sqrt{5} = (10 \times 2.235) = 22.35\)

Workspace


Tags:  IBM

3 / 72

 If the product of three consecutive positive integers is 15600 then the sum of the squares of these integers is

Answer: Option D

Explanation:

Here is no explanation for this answer

Workspace

4 / 72

 The minimum possible value of the sum of the squares of the roots of the equation x^2 + (a+3)x - (a-5) = 0 is

Answer: Option C

Explanation:

let x and y be the two roots of the equation.

x+y=-(a+3)

x*y=-(a+5)

now, x^2 + y^2 = (x+y)^2 - 2x*y

                        = a^2 + 9 + 6a + 2a + 10

                        = a^2 + 8a + 19 = (a+4)^2 +3


the minimum value of this could be when (a+4)^2=0 at a=-4

therefore, minimum value is 3.

Workspace

5 / 72

 The cube root of .000216 is:

Answer: Option B

Explanation:

\( (.000216)^{\frac{1}{3}} = \left(\frac{216}{10^{6}}\right)^{\frac{1}{3}}\)
= \(\left(\frac{6 \times 6 \times 6 }{10^{2} \times 10^{2} \times 10^{2}}\right)^{\frac{1}{3}}\)
= \(\frac{6}{10^{2}}\) = \(\frac{6}{100}\) = 0.06

Workspace


Tags:  No Tags on this question yet!

6 / 72

 What should come in place of both x in the equation \(\frac{x}{\sqrt{128}} = \frac{\sqrt{162}}{X} \).

Answer: Option A

Explanation:

Let \(\frac{x}{\sqrt{128}} = \frac{\sqrt{162}}{X}\)
Then\( x^{2} = \sqrt{128 \times 162}\)

=\( \sqrt{64 \times 2 \times 18 \times9} \)

=\( \sqrt{8^2 \times 6^2 \times 3^2} \)

= \(8 \times 6 \times 3\) = 144.

x =\( \sqrt{144}\) = 12.

Workspace


Tags:  No Tags on this question yet!

7 / 72

 The least perfect square, which is divisible by each of 21, 36 and 66 is:

Answer: Option A

Explanation:

L.C.M. of 21, 36, 66 = 2772.

Now, 2772 = \(2 \times 2 \times 3 \times 3 \times 7 \times 11\)

To make it a perfect square, it must be multiplied by \(7 \times 11\).

So, required number = \(2^2 \times 3^2 \times 7^2 \times 11^2\) = 213444

Workspace


Tags:  No Tags on this question yet!

8 / 72

 \(\sqrt{1.5625} = ?\)

Answer: Option B

Explanation:

Here is no explanation for this answer

Workspace


Tags:  No Tags on this question yet!

9 / 72

 If a = 0.1039, then the value of \(\sqrt{4a^2 - 4a + 1} + 3a\) is:

Answer: Option C

Explanation:

\(\sqrt{4a2 - 4a + 1} + 3a = \sqrt{(1)^2 + (2a)^2 - 2 x 1 \times 2a }+ 3a\)

= \(\sqrt{(1 - 2a)^2} + 3a\)

= (1 - 2a) + 3a

= (1 + a)

= (1 + 0.1039)

= 1.1039

Workspace


Tags:  No Tags on this question yet!

10 / 72

 If \(x = \frac{\sqrt3 + 1}{\sqrt3-1}\) and \(y = \frac{\sqrt3 - 1}{\sqrt3+1}\) , then the value of \((x^2 + y^2)\) is:

Answer: Option C

Explanation:

\(x =\frac{(\sqrt3 + 1)}{(\sqrt3-1)} \times\frac{(\sqrt3 + 1)}{(\sqrt3+1)}= \frac{(\sqrt3 + 1)^2}{3-1} = \frac{3 + 1 + 2\sqrt3}{2} = 2 +\sqrt 3.\)

\(y = \frac{(\sqrt3 - 1)}{(\sqrt3+1)} \times \frac{(\sqrt3 - 1)}{(\sqrt3-1)}= \frac{(\sqrt3 - 1)^2}{3-1} = \frac{3 + 1 - 2\sqrt3}{2} = 2 -\sqrt 3.\)

\(x^2 + y^2 = (2 + \sqrt3)^2 + (2 - \sqrt3)^2\) = 2(4 + 3) = 14

Workspace


Tags:  No Tags on this question yet!